Analysis Of The Effectiveness Of The Website-Based Lecturer Performance Assessment System And Human Resource Development At STIE Miftahul Huda - Sugito, Asep; Nurzaman, Fahrizal; Hamjah, Hamjah; Munir, Subhi (Pascasarjana STIE Miftahul Huda, 2024)
Along with the development of the era, technology is developing very rapidly and affecting all lines. Companies can take advantage of this by using digital information systems such as employee performance appraisals whose data can be used for evaluation. In educational institutions, technological developments also have a lot of influence and make work easier. The object of this study is the Miftahul Huda Subang College of Economics, the intent and purpose of this study is to analyze the effectiveness of lecturer performance assessments and website-based human resource developers. The research method used is a qualitative descriptive method. This analysis is strengthened by existing sources adapted from research journals and websites regarding performance appraisal systems, human resource development and the use of digital technology. Thus, it can be concluded that the performance appraisal system can help the process of human resource development, assisted by digital technology that is utilized properly.